2009
DOI: 10.1128/aem.01571-08
|View full text |Cite
|
Sign up to set email alerts
|

Differential Listeria monocytogenes Strain Survival and Growth in Katiki, a Traditional Greek Soft Cheese, at Different Storage Temperatures

Abstract: Katiki Domokou is a traditional Greek cheese, which has received the Protected Designation of Origin recognition since 1994. Its microfloras have not been studied although its structure and composition may enable (or even favor) the survival and growth of several pathogens, including Listeria monocytogenes. The persistence of L. monocytogenes during storage at different temperatures has been the subject of many studies since temperature abuse of food products is often encountered. In the present study, five st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 27 publications
0
18
0
8
Order By: Relevance
“…This was something quite expected, given the well-known greater capability of L. monocytogenes to adapt to survive and grow under a wider range of environmental conditions than S. enterica (18). In order to discriminate between the three different L. monocytogenes strains with regard to their ability to contribute to the formation and maintenance of the mixed culture biofilm communities (mono-/dual species) as well as to their antimicrobial recalcitrance, a promising PFGE approach, already used by our team (15,34), was followed. In this study, PFGE analysis revealed interesting information regarding strain occurrence following the different treatments (control, BC, NaClO, PA, and HP-PA) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This was something quite expected, given the well-known greater capability of L. monocytogenes to adapt to survive and grow under a wider range of environmental conditions than S. enterica (18). In order to discriminate between the three different L. monocytogenes strains with regard to their ability to contribute to the formation and maintenance of the mixed culture biofilm communities (mono-/dual species) as well as to their antimicrobial recalcitrance, a promising PFGE approach, already used by our team (15,34), was followed. In this study, PFGE analysis revealed interesting information regarding strain occurrence following the different treatments (control, BC, NaClO, PA, and HP-PA) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…La listeriosis no invasiva se manifiesta por síntomas de gastroenteritis (1,5,28,43), como diarrea, fiebre, cefalea y mialgias, y su periodo de incubación es corto (1,4,13,15,19,21,28,(43)(44)(45) Los alimentos considerados de alto riesgo para contraer listeriosis son los listos para el consumo (1,5,(9)(10)(11)16,17,28,(30)(31)(32)34,47,50,(63)(64)(65)(66). Ésta es una categoría amplia y heterogénea de alimentos (incluye bebidas) que no van a tener ningún proceso de cocción antes de su consumo, o que aparentemente son aptos para el consumo sin cocción (5,16), y varían de unos países a otros en relación con los hábitos alimentarios, la disponibilidad de la cadena de frío y la temperatura máxima en el punto de venta (1,5).…”
Section: Los Centers For Disease Control and Preventionunclassified
“…Con la clasificación alimentaria expuesta anteriormente, el criterio establecido en los Estados Unidos para aceptar como inocuos los alimentos listos para el consumo en los que puede crecer L. monocytogenes, es de cero tolerancia (10,16,47,48,65,68,69). Europa acepta niveles hasta de 100 unidades formadoras de colonias (UFC) para algunos alimentos que no estén destinados a poblaciones vulnerables (47).…”
Section: Los Centers For Disease Control and Preventionunclassified
See 1 more Smart Citation
“…In severe cases, this pathogen has been shown to enter the central nervous system (CNS). Usually, Listeria monocytogenes is ingested from contaminated food, particularly seafood, soft cheeses, and meat, being that this organism grows well at a wide range of temperatures [3]. From a cellular perspective, this pathogen has developed an array of molecular mechanisms by which it is able to invade a host cell, thrive and replicate before migrating to subsequent cells all while evading the immune system of the host organism [4].…”
mentioning
confidence: 99%